The Life and Work of Muhammad Ibn Jarir al-Tabari - Samee-Ullah Bhat (Khazanah Pendidikan Islam, 2022)
The third century of the Islamic era was a period of great intellectual attainments. It was in this period that some of the highest intellectual luminaries had risen on the horizon of Islamic learning, whose multiple contributions to multiple themes of Islam guided the later Muslim writers in diverse branches of knowledge. Abu Ja’far Muhammad Ibn Jarir al-Tabari was one of them who was a prolific writer, a Qur’anic exegete, a jurist, a traditionist and a historian and who produced prodigious works on all themes of Islamic learning including his work on Islamic history, Tarikh al-Tabari which has become an important source of information for many generations of historians of Islam. His second most influential and best known work is his work on Qur’anic commentary known as Tafsir al-Tabari which explains the text (sometimes word by word) based on its historical and lexicographical explanations. Miskawayah, Ibn Athir and Abul Fida were among the few Muslim historians who referred to the works of al-Tabari.  He learnt fiqh and jurisprudence from various teachers and contributed a lot to the science of Islamic jurisprudence by writing a number of prominent works. Therefore, this research paper will focus on the on the life of Abu Ja’far Muhammad Ibn Jarir al-Tabari. This research paper will also explore his contributions to different fields of knowledge through his eminent works keeping in view the descriptive as well as analytical methodology.